Interculturalidade no ambiente empresarial: relações entre brasileiros e estrangeiros na Volkswagen/Audi de São José dos Pinhais-PR - Trevisan, Lino (2001)
This investigation started from an interest to study the intercultural relationships between Brazilian and foreign workers in an automobile multinational company located in the outskirt area of Curitiba. The company chosen to be the setting of the research was Volkswagen/Audi located in São José dos Pinhais. The objective of this investigation was to identify difficulties employees faced in the intercultural relationships and the strategies they used to overcome the problems. Semi-structured interviews were used to collect data since this study was designed in a qualitative paradigm. Fifteen Brazilian workers and ten expatriates of the production sector and administrative department were interviewed. The concepts behind this study are the cultural, cultural diversity, intercultural relationships and organizational culture concepts. In order to better understand the representations of the two main groups interviewed - Brazilians and Germans - brief features of the culture and organizational culture of Brazil and Germany were raised. In the results of the research, Brasilian representations weere shown followed by the "expatriates". Afterwards, these representations were analyzed using the concepts which support this study showing similarities and differences of representations of the two groups interviewed concerning their intercultural relationsships in the company. The representations were grouped in blocks and organized in items, the most revealing characteristics of the opinions mentioned by the interviewees were reunited and which meets the objetive of this study. Therefore, in this investigation some general considerations were made, followed by the presentation of the difficulties identified by the employees in the intercultural relationships, and after that, the strategies used by the group to overcomme the problems. Finally, reciprocal representations of "we ant "they", which were found in the interviews of the two groups, were presented. The discussion of these representations and the attempt to analyze them is a new interpretation done by the researcher. In sum, this study is the interpretation of interpretations.